N-acetyltransferase 1*10 genotype in bladder cancer patients. Issue 7 (18th April 2017) - Höhne, Svetlana; Gerullis, Holger; Blaszkewicz, Meinolf; Selinski, Silvia; Hengstler, Jan G.; Otto, Thomas; Golka, Klaus
ABSTRACT: In a large bladder cancer study in the greater Berlin area with 425 cases and 343 controls, the haplotype N-acetyltransferase 1*10 ( NAT1*10 ) was associated with a decreased bladder cancer risk. In a recently published meta-analysis, results of the studies were found to be inconclusive. Therefore, the aim of this study was to investigate the frequency of NAT1*10 in bladder cancer patients and controls recruited in an area without industries reported to be associated with increased bladder cancer risk. Rs1057126 (1088 T > A) and rs15561 (1095 C > A) were determined in 412 bladder cancer patients and 415 controls without a known history of malignancies. With these two single-nucleotide polymorphisms (SNP), it was possible to distinguish between NAT1*4 (wild type), NAT1*3 (1095 C > A), and NAT1*10 (1088 T > A, 1095C > A). The frequencies of the determined NAT1 haplotypes did not differ markedly between cases and controls: NAT1*4 : 74%, NAT1*3 : 6%, NAT1*10 : 20%. Bladder cancer risk was not significantly modulated by NAT1*10/*10 (OR 1.03, 95% CI 0.71–1.48) but was higher for NAT1*3/*3 genotypes (OR 2.05, 95% CI 1.32–3.21). In contrast to the Berlin study from 2001, data in present study demonstrated that NAT1*10 haplotype was not associated with a significantly decreased bladder cancer risk. This may be due to local effects in the greater Berlin area, particularly at the time of investigation. The findings of the present study are in agreement with observations of a recently published meta-analysis which also showed no relevant impact of NAT1*10 haplotype on bladder cancer risk. The impact of the rare NAT1*3/*3 genotype was significant but this may be attributed to rarity without major practical relevance.